An overview of international and national law issues arising from the development of Carbon Capture & Storage (CCS) in South Africa - Herbstein, Tom (Centre for Law and Society, 2026)
If the growth in greenhouse gas (GHG)1 emissions continues unabated, the atmosphere is heading towards trebling its stock of GHGs by the end of the century.2 This is the view of the 2006 British government commissioned Stern Report. Amongst many other equally serious changes to the climate, there is a 50% risk that temperatures will rise by up to 5 o C around the planet. At the current rate, according to the Stern Report, a rise of 2-3 o C is foreseeable within the ‘next fifty years or so'. This would lead to increased flooding, decreased water supplies, increased pressure on coastal areas, hundreds of millions of people displaced and unable to produce or purchase sufficient food, and an estimated 15 – 40 % of the world's flora and fauna would be wiped out.3